Effects of Parental Health Education Program on Complications of Circumcision among Children in a Tertiary Care Hospital - Saha, Nirupama; Haque, Md Sajedul; Al Faisal, Md Abdullah; Shahabuddin, Sakib Bin; Zahid, Mirza Kamrul (Medicine Today, 2026)
Introduction: Circumcision in male children, however, is a commonly practiced surgical procedure, but still, remains a matter of great concern for parents/caregivers particularly regarding complications and caring for their children only because of their lack of knowledge. Parental health education programs might be an effective means to minimize the complications while enhancing better outcomes. Methods: This prospective type of educational interventional study was carried out among a total of 140 participants (parents/ caregivers- the mean age of whom was 35.34(SD±5.445 years) whose children (only male) were of 1-14 years old, eligible for circumcision selected employing purposive sampling technique. A specifically designed data collection sheet based on a set of questionnaires including both closed (yes/no) and open-ended questions before and after the program was used for data collection and data was analyzed with SPSS version 23. Results: Before the health education program, out of a total of 140 parents, 111(79.3%) did not have any idea about the health education program on circumcision. 95(67.9%) were almost unaware of solving any post-operative problem/complication. 67(47.5%) & 93(66.4%) respectively had no idea & lack of knowledge in caring of their children. Contrary to this, after the health education program, (51.4%), (45.7%), (47.1%), (48.6%) & (54.4%) respectively out of 140(100%) participants, strongly acknowledged the effectiveness of the education program in perspective of care of their children, in the easy handle of their children, in the identification of child problem easily, in coping up with their children along with anxiety reduction and appreciation in child care. 90(64.3%), & 80(57.1%) expressed a high level of benefits & satisfaction. Besides, 96(68.6%) needed follow-up visits after 7 days, and 100(71.4%) required only single-time visits. Altogether, around 63.7% of caregivers strongly recommend establishing a parental health education system before circumcision of the children. Conclusions: Parental health education program before circumcision has tremendous success in augmenting the knowledge, awareness, and confidence level of parents regarding caring for their children and thus reducing complications along with minimizing the burden of hospitals after circumcision. Medicine Today 2026, Vol.38 (1): 117-122